English as a Coding Catalyst: Exploring Its Impact on Basic Programming Learning Outcome in Health Information Management - Kusumawati, Erna Adita; Sutrisno, Trismianto Asmo; Wengker, Wengker (Utamax : Journal of Ultimate Research and Trends in Education, 2024)
This study addresses a critical gap in Health Information Management (HIM) education by exploring the relationship between English proficiency and basic programming learning outcomes, an area that has been underexplored despite the English-based nature of programming languages. Given that HIM professionals are increasingly expected to possess programming skills, understanding the role of English ability in this context is essential. A correlational research design was employed to examine this relationship, with statistical analysis including descriptive computations (mean, mode, median, variance, and standard deviation). Normality tests revealed non-normal data (p = 0.018), while linearity was confirmed (p = 0.154). The Spearman’s Rho correlation test indicated no significant correlation between English ability and basic programming learning outcomes (p = 0.174). Although no direct correlation was found, the study highlights the pivotal role that English still plays in programming education, particularly through English for Specific Purposes (ESP) courses, which remain essential in vocational higher education. These findings contribute to a better understanding of the factors influencing programming education in HIM programs, offering valuable insights for curriculum development and teaching strategies. The results suggest that while English proficiency may not directly impact programming success, its integration into the curriculum is still important for fostering digital competence. In a broader context, this study has implications for refining HIM education, enhancing pedagogical approaches, and strengthening student support services, ultimately contributing to the development of healthcare professionals who are both digitally literate and linguistically adept.